Implementation Of Development In Sudimoro Village, Bululawang Sub-District Towards Socio-Economic Changes In The Community - Suryo Hartoko Minarwanto; Didik Supriyanto; Deden Faturohman (Publikasi Indonesia, 2023)
The issue of village development is an important matter because this matter is often used as a benchmark to measure the ability of the government apparatus in carrying out the main obligations of the body or institution that provides services. The ruler of Sudimoro Village, Bululawang District, Malang Regency is trying to carry out development obligations by using the resources they have in the maximum way. One perspective that needs to be reflected in hamlet development activities is being able to provide satisfying results by improving the socio-economic life of the residents. This research intends to identify and analyze the impact of the hamlet development application on socio-economic changes in the community. The type of research used is descriptive qualitative research, the research location is Sudimoro Village, Bululawang District, Malang Regency and the research focus is 1). An Ordinary Reflection of Sudimoro Village, 2). Sudimoro Hamlet Regime 3). Development Application. 4). Consequences of Development on Socio-Economic Citizens. Analysis of the information in this research consists of 3 activities that are interactive, namely: Information reduction, Data presentation and Drawing conclusions. The application of development policies in Sudimoro village is carried out by programming and agreements between the authorities and residents through the Village Representative Body. The development budget comes from the encouragement of the authorities and self-help citizens. Development activities in the village of Sudimoro have generally produced quite good results, especially in increasing the socio-economic conditions of the residents, indicated by the fulfillment of the construction of tools and infrastructure for worship, development of learning, sports equipment and others that are sufficient. The economic aspect is signaled by the people's livelihoods increasing and running easily. Per capita income of the head of the family has increased quite well.